Figuring Atlantic Legacies: Impossible Archives, Missing Histories, Literary Counter-Memories - Iuli, Cristina (Review of International American Studies, 2017)
Cristina Iuli Università degli Studi del Piemonte Orientale, Dipartimento di Studi Umanistici Figuring Atlantic Legacies: Impossible Archives, Missing Histories, Literary Counter-Memories Abstract: This paper considers how neo- or trans- Atlantic studies conceives of the Atlantic and its legacies in relation to the idea of the archive, that is, of a body of works related to traces of a trans-Atlantic American past, to its principle of organization and analysis for literary studies, and to the critical descriptions of American Cultures in the context of a long trans-Atlantic network. It addresses how recent works on critical race studies and decoloniality, on performativity and memory and on comparative circum-Atlantic spectrality frame an original way to address how the literary imagination challenges the historical voids produced by modern Western amnesia. Keywords: trans-Atlantic; archive; critical memory; American literature